Perlindungan Hukum Terhadap Eksploitasi Jam Kerja Mahasiswa Magang - Rahmadia, Mohamad Haikal (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Internship is an activity that is usually carried out by students or new graduates who aim to gain work experience in a company or organization. It is common for students who are doing internships to be exploited for their labor hours. Exploitation practices can occur in various ways that are unfair and detrimental to students. One form of exploitation is assigning overtime tasks without any compensation or additional wages that should be received by them. This research aims to formulate the existing laws and regulations in Indonesia related to the protection of the rights of student interns.